Sistem Informasi Bimbingan Skripsi Menggunakan Metode Rapid Application Development Berbasis User Centered Design - Mochammad Alif Kurniawan; Iskandar Fitri; Deny Hidayatullah (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Thesis is the result of a scientific research paper written and adapted to the scientific rules that apply in writing and the process of working on a thesis, usually students are guided by two supervisors. Because during the pandemic and the difficulty of consulting with supervisors and the establishment of health protocols to avoid the impact of the spread of the COVID-19 virus, the author intends to build a Thesis Guidance Information System application that can be accessed online and based on a website and facilitates the thesis implementation process. Features contained in the system include students who can submit ideas and thesis titles and can see notifications of ideas and thesis titles being rejected or not. Students who carry out theses can be ensured that they are supervised by their supervisors, therefore supervisors can guide their students using the application and can carry out online sessions and seminars. The thesis guidance information system is designed using the Model View Controller architecture which separates the user interface, data and control. This object-oriented system development model uses the Unified Modeling Language model which aims to analyze and model applications designed using Model View Controller-based architecture. The software development method used in the development of this system is Rapid Application Development because it has relatively simple features. The User Centered Design approach is that users in every stage of system development are also involved, so that the system formed can be used according to system needs.